Brain amyloid load, subjective memory complaints, and cognitive trajectories in older individuals at risk for dementia - Saadmaan, Gazi; Hall, Anette; Ngandu, Tiia; Kemppainen, Nina; Mangialasche, Francesca; Wittenberg, Gayle M.; Matton, Anna; Rinne, Juha O.; Kivipelto, Miia; Solomon, Alina (WILEY, 2025)
Background and Purpose: This study evaluated associations of brain amyloid with 2-year objective and subjective cognitive measures in a trial-ready older general population at risk for dementia.
Methods: Forty-eight participants in the Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability underwent C-11-Pittsburgh compound B (PiB) positron emission tomography (PET) scans and assessment of cognition (modified Neuropsychological Test Battery [NTB]) and subjective memory complaints (Prospective and Retrospective Memory Questionnaire).
Results: Mean age was 71.4 +/- 5.06 years, and 20 participants (42%) had positive baseline PiB-PET scans. Amyloid positivity was associated with lower NTB executive function at baseline and less favorable 2-year NTB total score and memory trajectories, but not with other objective or subjective cognitive measures. Overall, there was little cognitive decline during 2 years.
Conclusions: Amyloid accumulation may affect objective but not necessarily subjective cognition from a very early at-risk stage, although substantial decline likely requires >2 years to occur.